Peningkatan Kinerja Karyawan Melalui Job Analysis - Hanuna Shafariah (Oikonomia: Jurnal Manajemen, 2022)
Purpose The study's objective is to investigate the impact of job analysis, which includes tasks, education, experience, and employee abilities, on employee performance both partially and simultaneously. Methodology This study employs quantitative and ex post facto methods. A total sample of 50 employees was obtained through the use of a simple random sampling technique. Existing data were collected using questionnaires and journal articles on research topics. Traditional assumption tests and multiple linear regression tests are used in data analysis techniques. Findings According to the findings, tasks have a significant positive impact on employee performance. Education has a big impact on employee performance. Work experience has a big impact on employee performance. Employee abilities have a significant and positive impact on employee performance. Employee performance is influenced by a combination of duties, education, experience, and abilities. Suggestion In order to improve employee performance, it is necessary to improve employees' abilities so that they can complete the details of tasks or jobs that have been assigned effectively and efficiently, as well as paying attention employees' educational backgrounds and experience when conducting employee searches in order for employees to be competent in their fields.